Towards time-of-flight PET with a semiconductor detector. (16th February 2018) - Ariño-Estrada, Gerard; Mitchell, Gregory S; Kwon, Sun Il; Du, Junwei; Kim, Hadong; Cirignano, Leonard J; Shah, Kanai S; Cherry, Simon R
Abstract: The feasibility of using Cerenkov light, generated by energetic electrons following 511 keV photon interactions in the semiconductor TlBr, to obtain fast timing information for positron emission tomography (PET) was evaluated. Due to its high refractive index, TlBr is a relatively good Cerenkov radiator and with its wide bandgap, has good optical transparency across most of the visible spectrum. Coupling an SiPM photodetector to a slab of TlBr (TlBr-SiPM) yielded a coincidence timing resolution of 620 ps FWHM between the TlBr-SiPM detector and a LFS reference detector. This value improved to 430 ps FWHM by applying a high pulse amplitude cut based on the TlBr-SiPM and reference detector signal amplitudes. These results are the best ever achieved with a semiconductor PET detector and already approach the performance required for time-of-flight. As TlBr has higher stopping power and better energy resolution than the conventional scintillation detectors currently used in PET scanners, a hybrid TlBr-SiPM detector with fast timing capability becomes an interesting option for further development.